Ruthenium complex exerts antineoplastic effects that are mediated by oxidative stress without inducing toxicity in Walker-256 tumor-bearing rats - Alves de Souza, Carlos Eduardo; Alves de Souza, Helen de Morais; Stipp, Maria Carolina; Corso, Claudia Rita; Galindo, Claudia Martins; Cardoso, Carolina Riverin; Dittrich, Rosangela Locatelli; de Souza Ramos, Edneia Amancio; Klassen, Giseli; Carlos, Rose Maria; Correia Cadena, Sílvia Maria Suter; Acco, Alexandra (Free radical biology & medicine, 2017)
The present study evaluated the in vivo antitumor effects and toxicity of a new Ru(II) compound, cis-(Ru[phen]2[ImH]2)2+ (also called RuphenImH [RuC]), against Walker-256 carcinosarcoma in rats. After subcutaneous inoculation of Walker-256 cells in the right pelvic limb, male Wistar rats received 5 or 10mgkg−1 RuC orally or intraperitoneally (i.p.) every 3 days for 13 days. A positive control group (2mgkg−1 cisplatin) and negative control group (vehicle) were also used. Tumor progression was checked daily. After treatment, tumor weight, plasma biochemistry, hematology, oxidative stress, histology, and tumor cell respiration were evaluated. RuC was effective against tumors when administered i.p. but not orally. The highest i.p. dose of RuC (10mgkg−1) significantly reduced tumor volume and weight, induced oxidative stress in tumor tissue, reduced the respiration of tumor cells, and induced necrosis but did not induce apoptosis in the tumor. No clinical signs of toxicity or death were observed in tumor-bearing or healthy rats that were treated with RuC. These results suggest that RuC has antitumor activity through the modulation of oxidative stress and impairment of oxidative phosphorylation, thus promoting Walker-256 cell death without causing systemic toxicity. These effects make RuC a promising anticancer drug for clinical evaluation. [Display omitted] •The compound RuphenImH (RuC) presented antitumor effect against the Walker-256 tumor in rats.•RuC induced oxidative stress and reduced the respiration of tumor cells.•RuC presented antitumor effect by i.p. but not by p.o. administration.•RuC has antitumor effect without causing systemic toxicity.